Precipitation forecast using RNN variants by analyzing Optimizers and Hyperparameters for Time-series based Climatological Data - Subha, J.; Saudia, S. (International Journal of Electrical and Computer Engineering Systems, 2024)
Flood is a significant problem in many regions of the world for the catastrophic damage it causes to both property and human lives; excessive precipitation being the major cause. The AI technologies, Deep Learning Neural Networks and Machine Learning algorithms attempt realistic solutions to numerous disaster management challenges. This paper works on RNN- based rainfall/ precipitation forecasting models by investigating the performances of various Recurrent Neural Network (RNN) architectures, Bidirectional RNN (BRNN), Long Short-Term Memory (LSTM), Gated Recurrent Unit (GRU) and ensemble models such as BRNN-GRU, BRNN-LSTM, LSTM-GRU, BRNN-LSTM-GRU using NASAPOWER datasets of Andhra Pradesh (AP) and Tamil Nadu (TN) in India. The different stages in the workflow of the methodology are Data collection, Data pre-processing, Data splitting, Defining hyperparameters, Model building and Performance evaluation. Experiments for identifying improved optimizers and hyperparameters for the time-series climatological data are investigated for accurate precipitation forecast. The metrics: Mean Absolute Error (MAE), Mean Squared Error (MSE), Root Mean Square Error (RMSE) and Root Mean Squared Logarithmic Error (RMSLE) values are used to compare the precipitation predictions of different models. The RNN variants and ensemble models, BRNN, LSTM, GRU, BRNN-GRU, BRNN-LSTM, LSTM-GRU, BRNN-LSTM-GRU produce predictions with RMSLE values of 2.448, 0.555, 0.255, 1.305, 1.383, 0.364, 1.740 for AP and 1.735, 0.663, 0.152, 0.889, 1.118, 0.379, 1.328 for TN respectively. The best performing RNN model, GRU when ensembled with the existing statistical model SARIMA produces an RMSLE value of 0.754 and 1.677 respectively for AP and TN.